Online voting for grassroots initiatives in California: electronic signature collection - Fabian Junior (GoAcademica Research & Publishing, 2022)
This article discusses the process of online collection of signatures for legislative proposals, taking as a starting point the current process for popular initiative in California. It describes how online signature of popular initiative petitions would work, as well as security issues and other objections to the collection of signatures via the internet could be addressed and, finally, the pros and cons of applying this method of collecting signatures to popular initiatives.